STRUKTUR DAN KATEGORI MANTRA PENGOBATAN DESA TELUK PINANG KABUPATEN INDRAGIRI HILIR - Rinaldi, Ego; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research id to described the structre magic medicine category in Teluk Pinang village Indragiri Hilir regency. Magic is kind of the oral literature that formed of poetry. Considering that magic is a poetry and a poetry has structures. So, this thesis analyzed the structure and magic medicine category. The existence of magic medicine is influenced of people reliance in Teluk Pinang village it self. The aim of this research is to described the opening and closing structure of magic and the magic category. The medicine is like handover,prerequment or sign and sacred. The method of this research is descriptive qualitative which use mimetic approach as a historic sosiological approach. The technique of data collecting is using observation, interview and documentation/recording. The data analysis is used the data reduction technique,data disiplay,condision drawing/verification. Based on the result of analysis,it can be concluded that the structures of magic medicine have form of opening part, content and closing the category of magic medicine grouped by handover, prerequirement,or sign and sacred.Keywords: The Structure,Category,Magic Medicine.